Digitalizing Urban Latin America - A New Layer for Persistent Inequalities? - Müller, Frank (2016)
Twenty years after Manuel Castells proclamation of the "Network Society" (1996), digitalization plays an ever-growing role in urban society. The "Smart City", for instance, promises more functional transport systems, access to internet technologies for all, and safe public spaces due to video surveillance 24/7. In addition, processing Big Data shall improve disaster prediction and community resilience in the age of real-time urbanism (Chandler, 2015), especially in the crisis-driven metropolises of the Global South. However, the free-to-access digital infrastructure has already been unmasked as just another myth (Coutard & Rutherford, 2016). Cities? digital "new skin" (Rabari & Storper, 2014) requires new theories and research methods to understand the spatial, social, political and cultural effects of digital technologies, the relationship between data and the urban, and the very notions of (big) data and connectivity.Urban Latin America occupies a privileged position in this research agenda. Latin American metropolises continue to show violent expressions of social inequalities such as socio-spatial segregation, racialized violence, police and military oppression, poverty, and environmental degradation. Yet, they are also key sites for contesting the neoliberal project (Miraftab et al., 2015). While digitalization promises to improve life quality, economic growth and human development, it is questionable whether digitalization helps to overcome historically established structural inequalities on a global and local scale. Does digitalization simply add a new layer to durable (Tilly, 1996) local and global north-south inequities, with investment opportunities for the few, consumerist life styles for the many, yet disconnections and digital exclusion for the all-time marginalized?This special issue of CROLAR DIGITALIZING URBAN LATIN AMERICA - A New Layer for Persistent Inequalities? provides a forum to discuss how digital technological innovation relates to social inequalities in urban Latin America. Which are the social, political, cultural and economic opportunities and obstacles that digitalization provides for more equal, just, participatory or inclusive urbanization? We invite reviews of empirically informed research on digitalizing urban Latin America, outlining potentials and pitfalls of digitalization in urban politics and planning, surveillance and securitization, (cyber)warfare and urban insurgencies, social and economic inclusion, community resilience, social protest and methods of doing research on and in cities.